1994
DOI: 10.1002/jnr.490380209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L‐glutamic acid on acid secretion and immunohistochemical localization of glutamatergic neurons in the rat stomach

Abstract: Glutamatergic neurons in the rat stomach were localized immunohistochemically using antibodies against L-glutamate (L-Glu) as well as glutamate synthesizing enzyme, glutaminase (GLNase). Myenteric ganglia and nerve bundles in the circular muscle and the longitudinal muscle were found to contain GLU- and GLNase-positive nerve fibers, while submucosa and mucosa were devoid of glutamatergic innervation. The distribution of glutamatergic neurons and their processes in both myenteric ganglia and circular muscle is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 17 publications
3
44
0
1
Order By: Relevance
“…Nicotinic cholinergic neurons have also been suggested to play a role in regulating the secretion of gastric acid [23]. Our recent investigation has confirmed that L-Glu reduces the oxotremorine-, histamine-, or gastrinstimulated gastric acid secretion, perhaps through its interaction with the non-NMDA ionotropic EAA receptors [28].…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…Nicotinic cholinergic neurons have also been suggested to play a role in regulating the secretion of gastric acid [23]. Our recent investigation has confirmed that L-Glu reduces the oxotremorine-, histamine-, or gastrinstimulated gastric acid secretion, perhaps through its interaction with the non-NMDA ionotropic EAA receptors [28].…”
Section: Introductionsupporting
confidence: 54%
“…The immunohistochemical procedure was similar to that described elsewhere [28]. Briefly, male Sprague-Dawley rats were initially anesthetized by an intraperitoneal injection of sodium pentobarbital (50 mg/kg), followed by perfusion with 1 liter saline at 37°C, and subsequent fixation with 4% paraformaldehyde in phosphatebuffered saline (PBS) (50 mM potassium phosphate buffer, pH 7.4, containing 0.9% NaCl) at 4°C.…”
Section: Immunohistochemical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In the CNS, electrophysiological L-Glu and L-Asp are less potent than NMDA due to their avid uptake by the tissue 102 , but there appears to be an absence of the uptake processes of these compounds in the myenteric plexus 95,96 . However, Glu and Asp are both involved in regulating acid secretion in the stomach, but the mode of action of each is different 652,658 . Asp was more specific than Glu in regulating acid secretion.…”
Section: Gastrointestinal Tractmentioning
confidence: 99%